O‘ZBEKISTON RESPUBLIKASI NOYOB VA YO‘QOLIB BORAYOTGAN SUTEMIZUVCHI HAYVONLARI. - Omonova N.R. , Omonova N.R.; Qarshiyeva F.A, Qarshiyeva F.A (Actual problems and prospects of the study of the fauna, 2024)
Due to the increasing human demand for natural resources, changes have occurred in the living conditions of animals on the Earth's surface. As a result, there has been a noticeable sharp decline in the population of many animal species.